Clinical profile of PCOS patients at a tertiary care center in Gandaki Province of Nepal - Pandey, Mahendra Raj (Asian Journal of Medical Sciences, 2020)
Background: Polycystic Ovary Syndrome is one of the most common cause of anovulation in women of reproductive age, with a prevalence of upto 10%. Oligomenorrhea, hirsutism and obesity together with enlarged polycystic ovaries are the diagnostic criteria of PCOS. These women are vulnerable to type II diabetes, dyslipidemia, premature arteriosclerosis, and endometrial carcinoma. Aims and Objectives: The aim and objective of this study was to see the various clinical profile of PCOS patients at a Medical College in Nepal and to make patients aware about the long term sequalae associated with it. Materials and Methods: This was a retrospective study conducted in the outpatient department of Obstetrics and Gynaecology at Manipal Teaching Hospital from January 2018 till June 2019. A total of 90 patients presenting with oligomenorrhoea, obesity, acne, infertility and hirsutism were included in the study. The exclusion criteria were young women who had their menarche less than 2 years back, women older than 45 years, and patients on exogenous estrogen or progesterone therapy. Results: Out of 90 patients studied, 37(41%) were married and 53(59%) were unmarried. There were many patients from urban compared to rural areas (67% vs 33%). Many patients were either overweight (22%) or obese (61%) and 6% of the patients were underweight. Mean age at the time of presentation was 31.66 years with many patients (37%) between 30-35 years age group. Majority of the patients were either oligomenorrhoeic or amenorrhoeic (78 %). Weight gain was present in 83% of the patients. Infertility was present in 81% of the married patients. Fifteen women (17%) had hypothyroidism and were receiving treatment for the same. Ultrasonography was done in all the patients and typical necklace pattern of follicular arrangement was seen in 70 (78%) patients. Conclusion: The diagnosis of PCOS can be reliably predicted with the help of clinical features and sonography in women according to Rotterdam criteria. Oligomenorrhoea or amenorrhea and weight gain were main symptoms in our patients. It is important to educate and make unmarried PCOS patients aware of its association with infertility and long-term medical problems.